The social impact advantage win customers and talent by harnessing your business for good - Boyea-Robinson, Tynesia (McGraw Hill, 2023)
"Our society is at a crossroads. It is no longer enough to have the best product or the most value add for your customers. Today consumers are considering more than just product quality and price. They are looking at how your company aligns with their values, how tapped into the social climate you are, and how authentic your social stances appear. To increase revenue and seize the competitive edge, your organization needs to embrace social causes and do it the right way"--